"Together we are better": Professional learning networks for teachers. (November 2016) - Trust, Torrey; Krutka, Daniel G.; Carpenter, Jeffrey Paul
Abstract: In recent years, many educators have turned to professional learning networks (PLNs) to grow in their craft with peers who are more accessible online because of reduced temporal and spatial constraints. While educators have cultivated PLNs, there is a dearth of research about the effects of PLNs. This manuscript reports the findings of a qualitative study that investigated PLN experiences through the analysis of survey data from 732 P-12 teachers. Data analysis suggests that the anytime, anywhere availability of expansive PLNs, and their capacity to respond to educators' diverse interests and needs, appear to offer possibilities for supporting the professional growth of whole teachers. These findings have implications for defining the present and future of teacher learning in a digital age. Highlights: Ninety percent of respondents defined PLNs as multifaceted systems. PLNs support affective, social, cognitive, and identity aspects of teacher growth. Almost all participants reported modifying teaching practices as a result of PLNs. Quarter of respondents credited PLNs as changing thinking about teaching. Respondents described PLNs' positive impact on student learning.